Impacts of Flood on Crop Production in Haor Areas of Two Upazillas in Kishoregonj - Khan, MNH; Mia, MY; Hossain, MR (Journal of Environmental Science and Natural Resources, 2012)
Haor is basin like structure where water remains either stagnant or in flash flooding condition during the months of June to November. In Bangladesh, haor areas are covered by Boro rice and produce a large amount. Severe flood damage this boro crop, so that the study was conducted to know the land use pattern and impact of flood on boro rice production. Both primary and secondary data were used for the study. Primary data were collected as survey sampling method (questionnaire, FGD, PRA etc.) from Itna and Mithamoin Upazilla where total respondents were 119. Secondary data were collected from Upazilla Administrations and Department of Agricultural Extension. Mainly descriptive statistics were employed to analyzing the data using MS Excel and SPSS. Most of the respondents were farmer. Major portion of their cultivable land are low land. Rabi is the only cropping season and during Kharif 1, and Kharif 2 lands became fallow due to inundate on flood water. In rabi season boro is the main crop and damaged by flash flood due to unavailability of controlling measures. Flood control measures would be taken to prevent huge loss of boro rice. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11581 J. Environ. Sci. & Natural Resources, 5(1): 193 198, 2012